The Influence of Social, Wellbeing and Financial Literacy on the Financial Burdens of the Sandwich Generation in Indonesia - Rachmawati, Lucky; Cahyono, Hendry; Hanifa, Nurul; Arisetyawan, Kukuh; Azhar, Nur Azirah Zahida Mohamad; Shakil, Nurul Syifaa Mohd; Rabbani, Muhammad Arkan (IKIP Widya Darma Surabaya, 2024)
Objective: In Indonesia, there are still many adults who generally still pay attention to and support their parents in addition to having to meet their children's needs. This is possibly because the community still maintains eastern customs. This study aims to: 1. Provide an overview of financial, social and welfare burdens financial literacy of the sandwich generation in Indonesia, 2. Knowing social influence, welfare and financial literacy towards the financial burden of the sandwich generation in Indonesia, 3. Develop recommendations looking at the problem conditions faced by the sandwich generation in Indonesia. Method: This study is a type of quantitative research using multiple linear regression analysis. Results: Household Decision Making and Self-treatment have a positive influence on the financial burden of the sandwich generation. Risk and Time Preferences have a negative influence on the financial burden of the sandwich generation. Ethnicity and Child Health Care do not significantly influence the financial burden of the sandwich generation. The Self Treatment has the largest influence compared to other variables. Novelty: This study makes a positive contribution for our understanding of the lives of the traditional sandwich generation in Indonesia. Ethnicity does not significantly influence the financial burden of the sandwich generation, this finding does not support research by Noor & Isa (2020), Do et al. (2014), and Marts (2013). Likewise, the Children's health care variable does not significantly affect the financial burden of the sandwich generation, these findings do not support research by Parker and Patten (2013).